2007
DOI: 10.1007/s10669-007-9005-z
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen recovery in an integrated system for wastewater treatment and tilapia production

Abstract: An integrated system, consisting of Up-flow Anaerobic Sludge Blanket (UASB)-duckweed-tilapia ponds was used for recovery of sewage nutrients and water recycling. A UASB reactor with 40 liter working volume was used as pre-treatment unit followed by a series of three duckweed ponds for nitrogen recovery. The treated effluent and duckweed biomass was used to feed fishponds stocked with Nile tilapia (Oreochromis niloticus). The UASB reactor was fed with raw, domestic sewage at 6 h hydraulic retention time. The th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
(53 reference statements)
0
6
1
Order By: Relevance
“…Actually, a better growth rate (1.56% day −1 ) and a lower FCR (1.4 ± 0.4) was observed in the present study than generally reported in other studies (Cruz & Ridha ; Ridha & Cruz ; El‐Shafai et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Actually, a better growth rate (1.56% day −1 ) and a lower FCR (1.4 ± 0.4) was observed in the present study than generally reported in other studies (Cruz & Ridha ; Ridha & Cruz ; El‐Shafai et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…However, to avoid accumulation of toxic concentrations of ammonia and nitrite in the water, it is necessary to integrate water treatment systems into recirculating aquaculture systems, such as various physical and biological filter systems (Ridha & Cruz ; Shnel et al . ; Davidson & Summerfelt ; El‐Shafai, El‐Gohary, Nasr, Steen & Gijzen ). The excess nutrients and organic matter produced in the recirculating aquaculture system can also be processed in ‛natural' ecosystems such as constructed wetlands (Lin, Jing & Lee ; Konnerup, Trang & Brix ), but these have relatively large footprints and do not grant any income for the farmer.…”
Section: Introductionmentioning
confidence: 99%
“…The application of Lemna gibba in a recirculation system decreased the feed conversion, increased protein efficiency ratio, and growth performance of Nile tilapia [28], [29]. Feed conversion in aquaculture industry profoundly needs certain consideration because it affects production cost directly.…”
Section: B Discussionmentioning
confidence: 99%
“…It is known that when nutrients from feeds are directly used by fish, the recovery rate is higher than when fertilisers are used (Table 4). Tacon et al (1995) in [44], found that supplementing feed in semi-intensive aquaculture farms improved N recovery, ranging from 5% to 25%, in fish. From Table 4, it can be argued that rabbit droppings must be better used by fish ponds than many other inputs to ensure a better environment for Nile tilapia growth.…”
Section: N and P Recovered By Harvested Productsmentioning
confidence: 99%